Malignant glomus tumor of the index finger - Tarun Kumar; Iffat Jamal; Jitendra Singh Nigam; Jagjit Kumar Pandey (University of São Paulo, 2021)
Glomus tumor (GT) is a benign mesenchymal tumor with an estimated incidence of 1.5 to 2% of soft tissue tumors. The majority of glomus tumors are benign and are mostly seen in the superficial skin & soft tissue of upper and lower distal extremity. The malignant variant of the glomus tumor is scarce. We report a case of a recurrent glomus tumor diagnosed in a 28-year-old male patient, who complained of painful swelling in the proximal phalanx of the right index finger. The magnetic resonance imaging of the hand revealed a well-defined multilobulated soft tissue mass at the palmar aspect of the 2nd digit along the shaft of the proximal phalanx. Histopathology revealed a well-circumscribed tumor arranged in solid sheets, nests and cords interconnect by vessels of varying size. The tumor cells were round to oval, showed moderate nuclear pleomorphism, eosinophilic cytoplasm, atypical mitoses (>5/10HPF), and necrosis. Immunohistochemically tumor cells reveal diffuse and strong cytoplasmic positivity with smooth muscle actin (SMA). Based on histomorphology and immunohistochemistry, a final diagnosis of malignant glomus tumor was made. We report this case due to its rarity, and it to be included among the differential if the lesion is painful and recurrent.